KECEMASAN STATISTIK DITINJAU DARI DUKUNGAN AKADEMIK - Suminta, Rini Risnawita (QUALITY, 2016)
This research aims to know the teacher academic support influence against the statistics anxiety and to know the influence of peer academic support against the statistics anxiety. The respondents in this study are 181 students of Islamic Psychology study program, Ushuluddin Department of State College on Islamic Studies (STAIN) Kediri. The data collection techniques used in this study is a questionnaire in the form of scale. There are two types of scales used in the process of collecting data, they are: (a) the statistical anxiety scale and (b) the scale of academic support. The data were analyzed using regression analysis. The results showed that the educator academic support gives a negative influence against the statistics anxiety (r =-0.47, R² = 0.17; p = 0.00). Similarly influential friends have a negative academic support against statistics anxiety (r =-0.22, R² = 0.02; p = 0.02).